2015
DOI: 10.1515/rjim-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

VEGF expression in pancreatic cancer and other malignancies: a review of the literature

Abstract: Angiogenesis is a crucial event for tumor growth and it is regulated predominantly by several different growth factors. Vascular endothelial growth factor protein family (VEGF) and its receptors are probably the most important tissue factors responsible for angioblast differentiation and tube formation. VEGF protein family currently comprises several members: VEGF (or VEGF-A), VEGF-B, VEGF-C and VEGF-D, VEGF-F, placental growth factor (PlGF), and their receptors VEGFR-1, VEGFR-2 and VEGFR-3. VEGF is a key angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 93 publications
(81 reference statements)
1
76
0
1
Order By: Relevance
“…However, according to the controversy reported on the use of growth factors such as BMPs for biomaterial doping, alternative osteoinductive factors without side effects must be investigated to warrant the safety of these innovative strategies . Accordingly, our group has just started a research program on the potential of nutrients (known for their ability to promote osteoblastogenesis and subsequent bone formation) as doping molecules for biomaterials.…”
Section: Optimization Of Bioactive Glass Hybridsmentioning
confidence: 99%
“…However, according to the controversy reported on the use of growth factors such as BMPs for biomaterial doping, alternative osteoinductive factors without side effects must be investigated to warrant the safety of these innovative strategies . Accordingly, our group has just started a research program on the potential of nutrients (known for their ability to promote osteoblastogenesis and subsequent bone formation) as doping molecules for biomaterials.…”
Section: Optimization Of Bioactive Glass Hybridsmentioning
confidence: 99%
“…Among these, the extracellular signal-regulated kinase (Erk) and its downstream vascular endothelial growth factor (VEGF) signaling pathway have critical roles [1618]. In particular, VEGF is probably the most important tissue factor and a key angiogenic growth factor that responsible for angioblast differentiation and tube formation [17]. Thus, VEGF overexpression not only considered as a diagnostic marker, but also a poor prognostic factor of PaC.…”
Section: Introductionmentioning
confidence: 99%
“…Expression level of VEGF represents an important marker for the detection of angiogenic diseases. VEGF aberrant expression was identified in most types of digestive cancers, including pancreatic cancer, being considered a diagnostic marker and a poor prognostic factor of the disease (14). In vitro studies demonstrated that VEGF stimulation led to a metabolic transition from mitochondrial oxidative phosphorylation to glycolysis in pancreatic cancer cell lines via HIF1α up-regulation (15).…”
Section: Angiogenesis and Inflammatory Angiogenesis And Inflammatory mentioning
confidence: 99%